A genetic study of Duchenne muscular dystrophy in West Midlands. Issue 1 (February 1981) - Bundey, S
Abstract : A study of Duchenne muscular dystrophy has shown an approximate prevalence of the disease among schoolboys to be 1 in 4000. Fifty-four families were available for genetic studies. In 19 families there were further affected cases and in 34 families the index patients was an isolated case. The proportion of affected brothers was 0.22 (11 of 50). There were 142 female relatives who had a risk of 1 in 10 or worse of being carriers: 66 of these were aged under 16. As genetic counselling is being increasingly requested by these families, and expansion of genetic services is envisaged. A genetic register, with frequent contact with families by ancillary staff, similar to that in Edinburgh, is considered desirable for the West Midlands.